Accumulation of metals and polycyclic aromatic hydrocarbons in agricultural soil after additions of street sediment in southern Ontario. (15th February 2019) - McDonough, Andrew; Baker, Scott; Grimm, Eric; Todd, Aaron; Luciani, Michael; Terry, Debbie
Abstract: Prior to 2012 street sediment from the Greater Toronto Area was being managed by a local authority and provided to rural landowners under the assumption it was clean fill. The aim of this study was to characterise the chemical and physical composition of that street sediment applied to an agricultural field in southwestern Ontario, Canada and determine if contaminants had migrated to native soil. Soil was sampled from an impact and a background location during the fall of 2016 at four soil depths (0–10, 10–20, 20–30 and 30–40 cm below the surface) to characterise texture, pH, organic content, recoverable metals and total polycyclic aromatic hydrocarbons (PAHs). Textural analysis revealed street sediment was dominated by very coarse and coarse sand which differed from the native silty clay loam and extended to 30 cm below the surface. Some PAHs, including benzo(a)pyrene (1.29 μg g −1 ) exceeded the typical regional background concentrations. A distinct pattern of high molecular mass PAHs in the native soil below street sediments suggests that PAHs have migrated to native soil. To our knowledge this is the first study to report PAH concentrations in street sediment in Ontario and to show their potential movement and introduction to native soil. Future studies should focus on transport mechanisms and understanding movement of PAHs in native coarse textured soil. Highlights: Street sediments were applied to agricultural soil. Polycyclic aromatic hydrocarbons (PAHs) moved from street sediment to native soil. Contaminant concentrations exceed management guidelines. First study to characterise movement of PAHs in street sediment in Ontario, Canada.